Contextual Meanings of the English Terms Used in Hotel - Arny Irhani Asmin (Universitas Cokroaminoto Palopo, 2019)
This paper presents the contextual meanings of the English terms used by the staff in Claro Hotel Makassar. The researcher observed three departments in a hotel; they are Housekeeping, Front Office and Food & Beverage department. The result of the research shows that there are many types of the English terms used in hospitality; some of the terms are categorized as the English special terms due to its contextual meaning. Furthermore, the researcher found that almost all staffs understand the terms even though they do not speak English fluently. However, for the new employer and trainee, most of them are somewhat distressed and said they did not know the terms because their educational background is not hospitality and the trainee said that some of the terms are not in their school textbook. Thus, it is essential for the English for Specific Purposes practitioners and particularly for the teachers of English for Hotel to understand and teach the contextual meanings of the particular English terms used in the hotel industry.